Marketing Strategy for Complete Feed of Beef Cattle - ., Sutawi; Wahyudi, Ahmad; Hendraningsih, Listiari; Arief, Sofyan (International Journal of Engineering and Technology, 2019)
Population and productivity of local beef cattle must be improved if beef selfsufficient was an important matter. Achieving beef selfsufficient would need procurement of feed in adequate quantity and quality. Complete feed was very important. The objectives of research were (1) to identify the factors of strength, weakness, opportunity, and threat of the marketing for beef cattle complete feed; and (2) to formulate the marketing strategy for beef cattle complete feed. Internal and external factors behind complete feed were identified with survey method against the groups of beef cattle farmers who were provided with complete feed sample. Marketing strategy was formulated with SWOT (Rangkuti, 2005). Based on the calculation of IFAS, it was shown that strength value of complete feed was 1.398. It was lower than weakness value of 1.981 with differential of both counted for -0.583. Result of EFAS indicated that opportunity value of 1.671 was lower than threat value of 1.951 with the differential of -0.280. The most suitable marketing strategy for complete feed was WT Strategy (minimizing weakness and avoiding threat). Some activities that must be done by complete feed producers were: (1) maximizing the use of farming wastes or residues available at place to suppress the cost of complete feed production, and (2) having a cooperation work with Gapoktan (Jointed Farmer Group) and KUD (Rural Unit Cooperative) as the distributor in the marketing of beef cattle complete feed.Â